Climate Strategy Between Ambition and Realism - Raad voor het Regeringsbeleid, Wetenschappelijke (WRR Rapporten, 2006)
This seminal and challenging analysis of the current global climate change suggests three courses of action for solving the climate problem: adaptation to the changed climate, selection of worldwide hopeful strategies for mitigation until 2050 and international coordination necessary to implement these strategies. This title is available in the OAPEN Library - http://www.oapen.org.